Toxicology New Aspects to This Scientific Conundrum - Soloneski, Sonia; Larramendy, Marcelo L. (IntechOpen, 2016)
This edited book, Toxicology - New Aspects to This Scientific Conundrum, is intended to provide an overview on the different xenobiotics employed every day in our anthropogenic activities. We hope that this book will continue to meet the expectations and needs of all interested in the implications for the living species of known and new toxicants and to guide them in the future investigations.